OPTIMALISASI PROSES PENGERINGAN MIE BELUT (Monopterus albus Zuieuw) INSTAN - Candra Candra; Juhana Suhanda; Rabiatul Adawyah; M. Rizky Indryawan (EnviroScienteae, 2021)
The aim of this research is to study the characteristic of instant eel noodles by drying process using oven and frying methods. Wet noodles from the data obtained are very susceptible to spoilage, so the processing of wet noodles is modified by carrying out the drying process. Instant eel noodles are a continuation process from the processing of wet eel noodles which are dried so that they become dry and easier to apply in the form of instant food. The study design was divided into 2 treatment groups, oven method (0, 1, 2 and 4 hours) and frying method (0, 1, 2 and 4 minutes). Each treatment was subjected to proximate characterization (moisture content, protein content, fat content, ash content and carbohydrate content (by different)) and organoleptic tests (appearance, color, aroma, texture and taste). The best treatment taken was frying drying for 4 minutes (A2) with a characteristic water content of 16.1%; protein content of 9,14%; fat content 18.11%; ash content 1.77%; 54.9% carbohydrate content. It is necessary to improve the oil drainage process after drying with the frying method to reduce the fat content of instant eel noodles.